Seasonal variation in cortisol biomarkers in Hispanic mothers living in an agricultural region. (July 2015) - Smith, Marissa N.; Wilder, Carly S.; Griffith, William C.; Workman, Tomomi; Thompson, Beti; Dills, Russel; Onstad, Gretchen; Vredevoogd, Melinda; Vigoren, Eric M.; Faustman, Elaine M.
Abstract Context: Characterization of stress exposure requires understanding seasonal variability in stress biomarkers. Objective: To compare acute and chronic stress biomarkers between two seasons in a cohort of rural, Hispanic mothers. Methods: Stress questionnaires and cortisol measurements (hair, blood and saliva) were collected in the summer and fall. Results: Cortisol biomarkers were significantly different and stress questionnaires were significantly correlated between seasons. Discussion: The variability in cortisol and relative stability of questionnaires between seasons may indicate that cortisol responds to subtle stressors not addressed in questionnaires. Conclusions: There are significant differences in stress biomarkers in our cohort between seasons.